Dual-Task Abilities During Activities Representative of Daily Life in Community-Dwelling Stroke Survivors: A Pilot Study - Deblock-Bellamy, Anne; Lamontagne, Anouk; McFadyen, Bradford J.; Ouellet, Marie-Christine; Blanchette, Andréanne K. (Frontiers in Neurology, 2022)
Background: In addition to several physical skills, being able to walk in the community, walking independently and safely in the community requires the ability to divide attention between walking and other tasks performed simultaneously. The aims of the present study were to measure cognitive-locomotor dual-task (DT) abilities in stroke survivors and to compare them with age- and gender-matched healthy individuals during activities representative of daily living. Methods: To assess DT abilities, all participants walked along a virtual shopping mall corridor and memorized a 5-item shopping list. Two levels of task complexity were used for the walking task (with or without virtual agents to avoid) and the cognitive task to recall a list of items (with or without a modification at mid-course). The assessment was conducted using an omnidirectional platform and a virtual reality (VR) headset. Locomotor and cognitive DT costs (DTC) were calculated as the percent change from single-task (ST) performance. Walking speed and minimal distance between the participant and the virtual agents were used to characterize locomotor performance. Cognitive performance was assessed by the number of correctly recalled items. One-sample Wilcoxon tests were used to determine the presence of DTC and Mann-Whitney tests were performed to compare DTCs between the 2 groups. Results: Twelve community-dwelling stroke survivors (60.50 years old [25th-75th percentiles: 53.50–65.75]; 5 women; 13.41 months post-stroke [5.34-48.90]) and 12 age- and gender- matched healthy individuals were recruited. Significant locomotor (6.54% to 10.78%; p-values: .006 to .010) and cognitive (10.56% to 33.33%; p-values: .002 to .037) DTCs were observed in participants with stroke in all DT conditions, except the simplest (no virtual agents, no modifications to the list). For the control group, only cognitive DTC were observed during DT the most complex DT condition. A group difference was detected in cognitive DTCs during the most complex DT condition (virtual agents and list modifications; p=.02). Stroke survivors had greater cognitive DTCs than the control group. Conclusions: Stroke survivors presented cognitive or mutual DT interferences while performing activities representative of daily living. Cognitive DTCs appeared to distinguish stroke survivors from controls.